Prospective Analysis, AHP, Causal Loop Diagram and Montecarlo Simulation to reduce costs of a metal-mechanic company. - Tello Zavala, Aurorita; Caruanambo Carhuayano, Gian Pierre; Julcamoro, Junior; Huancahuire Gamboa, Leslie; Tiznado Rojas, Walter Enrique; Oblitas Cruz, Jimy Frank (LACCEI, 2024)
The project focuses on addressing the current and future challenges of a metal-mechanical company. A prospective analysis and casual diagrams were performed to propose optimal solutions oriented toward continuous improvement. The goals established in this investigation were reorganizing the physical space to maximize efficiency, implementing a preventive maintenance plan for equipment, addressing the environmental impact of noise through acoustic insulation, improving inventory logistics management with ABC methodology, and using a Monte Carlo simulation for cost reduction. The discussion of results highlights the performance, such as improved operational efficiency and productivity with the new layout, reduced downtime with preventive maintenance, regulatory compliance and welfare generated by the acoustic insulation, and accuracy in inventory management with the ABC methodology. In conclusion, the implementation of these solutions has proven to be fundamental for the integral optimization of the company, effectively addressing the identified challenges.